2012
DOI: 10.1186/1471-2229-12-147
|View full text |Cite
|
Sign up to set email alerts
|

Proteome characterization of developing grains in bread wheat cultivars (Triticum aestivum L.)

Abstract: BackgroundThe analyses of protein synthesis, accumulation and regulation during grain development in wheat are more complex because of its larger genome size compared to model plants such as Arabidopsis and rice. In this study, grains from two wheat cultivars Jimai 20 and Zhoumai 16 with different gluten quality properties were harvested at five development stages, and were used to displayed variable expression patterns of grain proteins.ResultsProteome characterization during grain development in Chinese brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 74 publications
(85 reference statements)
5
77
0
Order By: Relevance
“…In this region both in Ciccio and in Svevo several spots, specific for milk stage, resulted more concentrated in the gel zone near pH 3, while at physiological stage the specific spots appeared in the basic zone of the gel (Figure 1) making us assume a possible change in the protein isoelectric point (pI) during grain filling. According to our results also Guo et al (2012) reported the presence of proteins near the acid zone of the gel in the early developmental stage, with the number of basic proteins increasing at maturity. Moreover in both cultivars there was one spot that seems to be a master spot at the beginning of a spot train.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…In this region both in Ciccio and in Svevo several spots, specific for milk stage, resulted more concentrated in the gel zone near pH 3, while at physiological stage the specific spots appeared in the basic zone of the gel (Figure 1) making us assume a possible change in the protein isoelectric point (pI) during grain filling. According to our results also Guo et al (2012) reported the presence of proteins near the acid zone of the gel in the early developmental stage, with the number of basic proteins increasing at maturity. Moreover in both cultivars there was one spot that seems to be a master spot at the beginning of a spot train.…”
Section: Resultssupporting
confidence: 50%
“…To better investigate the effects of environment on proteins and genes that may be involved in determining yield and quality, proteomic and transcriptomic approaches result useful (Altenbach, 2012). However, also due to the various post-translational modifications of proteins that occur as grain develops, the accumulated amounts of a large proportion of proteins are often poorly correlated with their corresponding mRNAs in expression profiles; for this reason a proteomic approach can be more valuable in monitoring developmental profiles (Guo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…None of the examined genotypes of durum wheat can be recommended for the simultaneous selection of genotypes with high content of albumins and good stability, because genotypes with high mean albumins content had unsatisfactory stability. The albumins content in bread wheat grains is not as stable across environments as that of the storage proteins according to Guo et al (2012). The inclusion of all climatic variables to the factorial regression led to the model (mt3, wmr, mnt2, mnt1) for bread wheat and to the model (pr2, sh1, mxt3, wmr) for durum wheat, which were obtained at the level of significance (P < 0.01) ( Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Guo et al (2012), several main groups of grain proteins were identified according to their functions, of which 3.4 % was involved in signal transduction including NDPK. NDPK might play an important role in signal regulation for grain development in wheat, because it was gradually down-regulated during grain development .…”
Section: Signaling Related Proteinsmentioning
confidence: 99%